PENGARUH COMPUTER ANXIETY, COMPUTER ATTITUDE DAN COMPUTER SELF EFFICACY TERHADAP MINAT MAHASISWA MENGGUNAKAN SOFTWARE AKUNTANSI - Mega Handayani; David Sulistiyantoro; Gerlan Haha Nusa (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2022)
The use of accounting software as part of the development of information technology requires a skill in order to function effectively. Meanwhile, computer skills can be affected by several factors, including computer anxiety, computer attitude and computer self-efficacy. Those factors will ultimately influence a person's interest in using accounting software. This study aims to empirically verify the affect of computer anxiety, computer attitude and computer self-efficacy on the interest of accounting students in the use of accounting software, such as MYOB, Accurate and Zahir. The method used in this study is a quantitative method by distributing questionnaires to the Accounting students at Universitas Jenderal Achmad Yani Yogyakarta. The questions presented in the questionnaire were measured using a Likert scale and analyzed using linear regression analysis in testing research hypotheses. The results of the research are that only the computer self-efficacy variable has been shown to have a positive effect on students' interest in using accounting software. While the other two variables, that are computer anxiety and computer attitude, were not shown to have an effect. Meanwhile, the three variables simultaneously have been shown to have an effect on students' interest in using accounting software.